Analisis Perbandingan Penerapan PP No. 23 Tahun 2018 Dengan PP No. 46 Tahun 2013 Tentang Pajak Panghasilan - Argo Putra Prima; Ferdila Ferdila (LPPM Universitas Putera Batam, 2022)
Activities of Micro, Small and Medium Enterprises that have a dominant existence in supporting the welfare of the community. Related to the importance of special attention to MSMEs in supporting the economy, the government issued PP No. 46 of 2013 for businesses with income below Rp 4.8 billion. With the enactment of this rule, it is hoped that it can help the community in paying their business taxes, namely 1% final tax of the turnover they get. From the analysis conducted by the researcher, in general, these two regulations have many similarities. However, what is significantly different is the latest rate that came into effect on July 1 2018 that the rate of corporate income tax with gross income has a rate of 0.5% which was originally 1% which has been in effect since 2013. So the government revised the tax rate rules for MSMEs from PP No. .46 of 2013 became Government No. 23 of 2018 with the latest tariff of 0.5%. Both of these rules are final, meaning they are calculated based on the gross amount directly. And the payment can be made via Electronic Deposit Letter. And if you have made a payment, it is considered to have been reported and there is no need to report it to the tax office or via other applications. With a rate of 0.5%, it is expected that taxpayers will always be obedient in reporting their taxes, including PT Bisnis Teknologi Manajemen as a taxpayer.